Problems of China’s Legal Supervision System on the Internet Medical Care Under the Background of 5G Medical Application - Qu Y; Liu R (Dove Medical Press, 2022)
Yunfeng Qu, Ruiyang Liu School of Law, Hainan University, Haikou, People's Republic of ChinaCorrespondence: Ruiyang Liu, School of Law, Hainan University, No. 58 Renmin Road, Meilan District, Haikou, 570228, People's Republic of China, Email lawliuruiyang@163.comAbstract: With the advent of 5G network technology and the maturity of medical applications associated with 5G, the Internet medical service industry is gradually developing. Given the COVID-19 pandemic crisis occasionally happened in China, hospitals were taken up most of the medical resources, the Internet medical care is seen as the alternative way for patients to access medical care and treatment. With the aid of 5G, patients nowadays can seek remote medical care, diagnosis, and surgery. However, this is not without any problems. The current legal supervision system in the Internet medical service industry is still incomplete, and ought to be augmented. This essay serves to identify and evaluate the loopholes existing in the legal supervision system in the Internet medical service industry, in the hope to improve the current system and ensure the safety of patients who are seeking Internet medical services.Keywords: internet medical care, legal supervision, 5G technology, remote surgery